IMPROVEMENT OF ENVIRONMENT QUALITY BY GREENERY RECOVERING - Radomska, Мargarita; Kumejko, Sofia; Shtelma, Kristina (Proceedings of National Aviation University, 2014)
Principal reasons of chemical pollution caused by the activity of filling stations, namely losses of hydrocarbon material, which takes place at transport operations and exploitation of imperfect equipment, have been analyzed. The primary sources of filling stations negative environmental impacts are shown to be storm waters, which wash off poured out petrochemicals from their territory, while direct environment pollution as a result of emergency overflows of petrochemicals is a rare phenomenon. It is indicated that the negative consequences of filling stations activity spread on atmospheric air, adjoining soils and water objects, including ground and underground water, and it is expressed in contamination of these environment components with petrochemicals and creation of threats for human health.